Nyekar Sekardadu Grave as The Formation of Community Collective Memory Coastal - Mawardani, Hesti Amelia; Mubaroka, Kholida Ulfi; Sadewo, FX Sri (ETNOSIA : Jurnal Etnografi Indonesia, 2025)
This study examines the tradition of nyekar makam Dewi Sekardadu as an element of collective memory in the coastal community of Sidoarjo, Indonesia, focusing on its transformation from a sacred spiritual practice to commercialized cultural tourism. Unlike existing literature, which generally focuses on traditional practices as static cultural artifacts threatened by modernization. This study reveals how the nyekar tradition dynamically adapts through economic integration while maintaining community relevance, introducing a new perspective by showing how collective memory sites can serve dual functions as both unifiers and dividers of communities, with some locations claiming authenticity a phenomenon that has been under-explored in Indonesian cultural tourism studies. Using a qualitative approach, this study was conducted in Kepetingan Village (Buduran Subdistrict) and Wunut Village (Porong Subdistrict) in Sidoarjo. Data was collected using in-depth interview with ten informants, consisting of two traditional community leaders and eight local residents who directly participate in the tradition, supplemented by participatory observation. The study shows significant transformations where spiritual values now account for only 15% of the tradition, while entertainment and economic aspects are dominant. This tradition operates as a habitus within the social arena of coastal communities, where various forms of capital (cultural, symbolic, social, and economic) interact and convert within the context of modernization, while the tomb of Dewi Sekardadu has become a contested site of memory, reflecting the complex dynamics of collective memory. This study contributes to an understanding of how collective memory is dynamically reconfigured through the interaction between changing social habitus and evolving economic arenas, representing adaptive mechanisms rather than threats to authenticity in Indonesian coastal communities.